Enhancing Pre-Service Teachers’ Understanding of Science Teaching through STEM Activities Integrated Inquiry Learning with Thai Context - Adchara Chaisri Khureerung; Thi Phuong Thao-Do (Journal of Educational Issues, 2024)
The objectives of this research were: 1) To develop and examine a learning model using STEM activities for pre-service science teachers, and 2) To study the condition and develop a learning model using STEM activities in science teaching integrated with Thai local context using schools and communities as bases. The target group of the research was 81 pre-service science teachers from 240 1st-4th years, obtained by purposive sampling, they are volunteer ones, who are interested in improving their teaching. The tools used in the research were lesson plans, questionnaires, field notes, and journal writing. The lesson plans included three STEM activities integrated into local settings that could be applied in science classrooms. The results were as follows: 1) The developed STEM learning model can be used as a guideline for teaching and learning with promising results; 2) The target group of pre-service science teachers had a significant improvement in their level of understanding of the science learning process in STEM activities. In the beginning, they received an average score of 17.28 on a scale of 50 and a standard deviation (SD) of 3.13 on STEM Learning Management Understanding Link-local context using schools and the community is the base, which could be interpreted as a low level. After teaching using these developed STEM activities, their average score was raised to 41.93 with the SD being 3.71, which could be interpreted as a high level. It could be concluded that the learning approach from this research is one approach that can improve teaching and learning management for pre-service science teachers.